Incidence and risk factors for secondary malignancy in patients with neuroblastoma after treatment with 131I-metaiodobenzylguanidine. (October 2016) - Huibregtse, Kelly E.; Vo, Kieuhoa T.; DuBois, Steven G.; Fetzko, Stephanie; Neuhaus, John; Batra, Vandana; Maris, John M.; Weiss, Brian; Marachelian, Araz; Yanik, Greg A.; Matthay, Katherine K.
Abstract: Several reports of second malignant neoplasm (SMN) in patients with relapsed neuroblastoma after treatment with 131 I-MIBG suggest the possibility of increased risk. Incidence of and risk factors for SMN after 131 I-MIBG have not been defined. This is a multi-institutional retrospective review of patients with neuroblastoma treated with 131 I-MIBG therapy. A competing risk approach was used to calculate the cumulative incidence of SMN from time of first exposure to 131 I-MIBG. A competing risk regression was used to identify potential risk factors for SMN. The analytical cohort included 644 patients treated with 131 I-MIBG. The cumulative incidence of SMN was 7.6% (95% confidence interval [CI], 4.4–13.0%) and 14.3% (95% CI, 8.3–23.9%) at 5 and 10 years from first 131 I-MIBG, respectively. No increase in SMN risk was found with increased number of 131 I-MIBG treatments or higher cumulative activity per kilogram of 131 I-MIBG received (p = 0.72 and p = 0.84, respectively). Thirteen of the 19 reported SMN were haematologic. In a multivariate analysis controlling for variables with p < 0.1 (stage, age at first 131 I-MIBG, bone disease, disease status at time of first 131 I-MIBG), patients with relapsed/progressive disease had significantly lower risk of SMN (subdistribution hazard ratio 0.3, 95% CI, 0.1–0.8, p = 0.023) compared to patients with persistent/refractory neuroblastoma. The cumulative risk of SMN after 131 I-MIBG therapy for patients with relapsed or refractory neuroblastoma is similar to the greatest published incidence for high-risk neuroblastoma after myeloablative therapy, with no dose-dependent increase. As the number of patients treated and length of follow-up time increase, it will be important to reassess this risk. Highlights: Multi-institutional review of neuroblastoma patients treated with iodine-131 metaiodobenzylguanidine ( 131 I-MIBG) therapy. Competing risk approach used to find cumulative incidence of second malignant neoplasm (SMN) from first MIBG. Cumulative risk of SMN after MIBG therapy was 14% at 10 years. Results similar to risk after myeloablative therapy; no dose-dependent increase.